Cultivation of Azolla Microphylla as an Alternative Feed for Goats in Kalikesur Village, Kedungbanteng District, Banyumas Regency: Budidaya Azolla Mycrophilla Sebagai Alternatif Pakan Ternak Kambing di Desa Kalikesur Kecamatan Kedungbanteng Kabupaten Banyumas - Adhi Susilo; Indah Setia Utami; Adi Suryanto (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
Kalikesur Village, located in the Kedungbanteng District of Banyumas Regency, possesses significant prospects in agriculture and animal husbandry. Typically, the villagers continue to rely on forage fodder, such as grass and agricultural waste, to feed their poultry and cattle. Hence, the objective of our community activity is to acquaint the inhabitants of Kalikesur Village with the Azolla plant as a substitute feed and as a material for bio-organic fertilizer. We also want to teach cultivating methods so that an Azolla business group can be established. Getting to know one another, sharing insights on the value and advantages of Azolla for animal feed and bio-organic fertilizers, constructing basic bio-flocks (ponds), learning how to cultivate and harvest Azolla, creating fertilizer with Azolla as a base, and initiating new Azolla marketing campaigns on social media were some of the activities that took place. One of the program's many results is the technology transfer for growing Azolla, which may be used as a bio-organic fertilizer and a nutritional feed alternative. Additionally, it creates instructions for growing Azolla and using it as bio-organic fertilizer and animal feed. Additionally, the program provides manuals on the business analysis of Azolla. It contributes to the increase in livestock production, thereby enhancing the income and welfare of community service partners and the surrounding region.